Smart revolution and metrology: A longitudinal science mapping approach. (December 2021) - Sousa, M.C.; Almeida, M.F.L.
Abstract: The aim of this study is two-fold. Firstly, it attempts to identify and visualize evolutionary pathways and scientific roadmaps focusing on the interplay between smart manufacturing and metrology as a research field. Secondly, it seeks to identify and visualize technological trends in this research field, i.e., the most productive themes, relevant thematic networks, and strategic diagrams based on the most cited articles in each theme for different time slices. A bibliometric analysis was conducted to assess all peer-reviewed documents indexed in the Web of Science database covering the focused research field over the 2010–2020 time frame. Based on a bibliographic data collection of 396 documents, it was possible to identify and visualize a longitudinal science map over this period, highlighting digital technology trends and identifying shifts in the boundaries of the focused emerging digital technologies applied to metrology and vice-versa, by revealing their interactions and convergence.